Permasalahan Pariwisata di Indonesia Tinjauan Literatur Sistematis - Yulistriani Yulistriani; Rudi Febriamansyah; Sari Lenggogeni; yuerlita yuerlita (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
This study presents a systematic literature review of scholarly research examining tourism development challenges in Indonesia from 2010 to 2025, based on publications indexed in ScienceDirect. Literature identification and selection were conducted in accordance with the PRISMA framework, while bibliometric mapping and thematic analysis were performed using Visualization of Similarities (VOS). The initial literature search was carried out in ScienceDirect using the keyword string “tourism AND problems in Indonesia”. A multi-stage screening and eligibility process followed this. The selected articles were organized using Mendeley Desktop and subsequently subjected to manual verification to ensure data validity, thematic relevance, and consistency with the research objectives. Only studies that met the predefined inclusion criteria were retained for further analysis. The validated dataset was then analyzed using VOSviewer to visualize thematic relationships and co-occurrence patterns among the main research topics. The resulting VOS maps were manually interpreted by examining the most frequently occurring keywords and their relational structures. Based on this analysis, the study identifies major patterns and research gaps that provide directions for future investigations into tourism-related challenges in Indonesia. Overall, the tourism issues identified in the literature were systematically classified into three primary dimensions: environmental, social, and economic issues.